The impact of teacher attitude and teaching approaches on student demotivation: Disappointment as a mediator - Tang, Yeyao; Hu, Jifan (Frontiers in Psychology, 2022)
Student KH- demotivation as a medium of instruction has attracted an increased attention of scholars, particularly in those countries where it is taught as a second or foreign language. While there is a consensus that proficiency in language brings several benefits, yet it is found that students are demotivated to learn in workplace environment. As a result, many studies have tried to investigate the factors that reduce the motivation to learn in work environment. Drawing on disappointment theory, this study aims to investigate why and how the discouraging attitude of a teacher and discouraging teaching approaches create negative emotions (i.e. disappointment), which in turn demotivates Chinese students with English as a medium of instruction. This study has adopted cross-sectional research design. The data were collected through a self-administered questionnaire survey from Chinese students (n=428) studying in different universities in China. The hypothesized relationships were tested through PLS-based SEM by using Warp-PLS 7.0 software. The findings show that KH- discouraging attitudes and discouraging teaching approaches are important determinants of student demotivation with workplace environment. The results also confirm that KH- disappointment is an important underlying mechanism in the relationship between exogenous and endogenous variables. The findings suggests that university administration should monitor the attitude of the International teachers as well as their teaching approaches in order to curb any potential threat to the student motivation. In this way, KH- disappointment with the teacher and teaching methodology can also be overcome, which will ultimately increase their motivation with good international workplace environment.